Military Criminal Sanctions and the Peculiarities Related to their Execution in Hungary (1930 – 1948) - József Pallo (Journal on European History of Law, 2024)
The goal of the author is to investigate a slightly obscure topic: the practice of interwar military justice in Hungary and its related questions, with an emphasis on matters concerning the peculiarities on how to implement them. The bill – which came into effect in 1930 – was born amidst uncommon historical conditions, since the Trianon Peace Treaty basically degraded Hungary into a quasi-numb entity. It is without a doubt that the decade-long consolidation – and its achievements – that came after can be regarded as one of the most prominently successful periods of the era’s political history. The historical pressure, the necessity of being able to defend ourselves along with the importance of national security demanded that our army remained intact, despite the prohibitions that surrounded its existence. This called for ensuring that the legal environment was modernized enough to be capable of supporting this goal. The system of regulations inherited from the Austro-Hungarian monarchy was subjected to scrutiny and as a result ended up as a state-of-the art framework that even surpassed the European standards it aimed to match. This paper, putting emphasis on the most important dogmatic junctions, will further review these regulations – substantive or procedural contents alike –. After a brief diversion towards taking a glimpse into the historical situation, we will introduce the system of sanctions and punishments pertaining to military personnel, and proceed with the regulations related to their implementation, which in turn will offer a glimpse into the contemporary philosophy that surrounded military justice and procedure. In accordance, further regulations containing provisions regarding infrastructure, personnel, accommodation, and institution security in general would emerge. The author of the article provides a summary of the most important current relevant legal provisions. It touches upon the military justice system and its subsystems, introduces the more substantive procedural rules, and concludes with an argument on practical implementation. It will also raise the theoretical question on a future independent regulation which would take place in accordance with the reforms of the Hungarian military and the national strategy on defense.